2017
DOI: 10.31018/jans.v9i4.1463
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of botanicals and fungicides against Rhizoctonia solani inciting sheath blight disease on Rice (Oryza sativa L.)

Abstract: Among the fungal diseases, sheath blight, caused by multinucleate Rhizoctoniasolani Kuhn (teleomorph: Thanatephorus cucumeris Donk), a ubiquitous pathogen, is an important fungal disease of rice ranking only after blast and often rivalling it. The potential losses due to sheath blight alone in India has been up to 51.3%. In this study an attempt was made to investigate the antifungal efficacy of botanicals viz., neem (Azadirachtaindica), tulsi (Ocimum sanctum), garlic (Allium sativum), onion (Allium cepa), gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
4
13
1
Order By: Relevance
“…The fungicides containing Tubeconazole and Carbendazim as active ingredients, shows highest degree of mycelia inhibitions as compared to others. The inhibitory effect of Carbendazim on R. solani has also been reported by Kumar et al (2017). Kadri and Kanzari (2018) also reported that carbendazim 50% WP and tebuconazole 25.9% EC among systemic fungicides gave maximum mycelial growth inhibition of 83.83 and 81.70 percent, respectively under laboratory conditions (Kadri and Kanzari, 2018).…”
Section: Resultssupporting
confidence: 53%
“…The fungicides containing Tubeconazole and Carbendazim as active ingredients, shows highest degree of mycelia inhibitions as compared to others. The inhibitory effect of Carbendazim on R. solani has also been reported by Kumar et al (2017). Kadri and Kanzari (2018) also reported that carbendazim 50% WP and tebuconazole 25.9% EC among systemic fungicides gave maximum mycelial growth inhibition of 83.83 and 81.70 percent, respectively under laboratory conditions (Kadri and Kanzari, 2018).…”
Section: Resultssupporting
confidence: 53%
“…Also, the EC50 values of triticonazole for isolates of F. graminearum ranged from 0.043 to 4.965 µg mL -1 (Burlakoti et al, 2010). Similarly, carbendazim effectively inhibited the mycelial growth and sclerotial production of R. solani at lower concentration (Sriraj et al, 2014;Kumar et al, 2017). Also, mycelial growth of F. graminearum was strongly inhibited by carbendazim (Ivic et al, 2011).…”
Section: In Vitro Activity Of the Fungicides On The Isolated Fungimentioning
confidence: 99%
“…Burlakoti et al (2010) suggested that triticonazole has the potential to control Fusarium diseases in field conditions if applied in a timely manner. Carbendazim was effective against R. solani at the lowest concentration by maximum inhibiting the mycelial growth and sclerotia formation (Sriraj et al, 2014;Kumar et al, 2017). Also, carbendazim has been widely used to control Fusarium diseases on several crops including wheat, showing a great capability to prevent Fusarium infections (Manasa et al, 2017;Mannai et al, 2018).…”
Section: Separately Effect Of the Tested Fungicides And Bioagents On mentioning
confidence: 99%
See 1 more Smart Citation
“…In well plate technique, 1 ml of the plant extract was added in the well on one side of the Petri dishes and on the other side, the discs of R. solani was placed. Petri plates containing sterile water in the well serves as a control [17].…”
Section: Screening Of Antifungal Activity Of Plant Extracts Against Fmentioning
confidence: 99%